Where Theory Meets Necessity: A Scientometric Review of Necessary Condition Analysis Applications - Ari Irawan; Taufiq Ismail (PINISI Discretion Review, 2026)
Necessary Condition Analysis (NCA) is gaining traction as a robust methodological approach for identifying the essential conditions required for a particular outcome to occur. While its use spans domains such as psychology, management, and tourism, systematic reviews remain limited, particularly those employing scientometric methods to map the intellectual structure of NCA applications. This review addresses that gap by analyzing the evolving landscape of NCA research across disciplines through a systematic bibliometric approach. Using data retrieved from the Web of Science Core Collection on January 6, 2026, the study analyzed 364 SSCI-indexed journal articles. Two bibliometric techniques were employed: bibliographic coupling to identify current and emerging thematic clusters, and co-word analysis to explore prospective research directions. Data visualization and network mapping were conducted using VOSviewer 1.6.20. Three key thematic clusters emerged in both analyses: digital consumer research, psychological conditions, and tourism and hospitality studies. Major trends revealed the integration of NCA with methods such as PLS-SEM and fsQCA, and its role in identifying non-compensatory conditions in innovation, adoption, and behavioral outcomes. The findings highlight the value of NCA in theory building and methodological advancement, offering unique insights into must-have conditions across fields and enhancing decision-making and research precision. Future research should pursue interdisciplinary integration, mixed-methods applications, and geographic diversification.